Digital Microfluidics for Isothermal Nucleic Acid Amplification: Exploring Sensing Methodologies - Coelho, Beatriz Jorge (2023)
Digital Microfluidics (DMF) has recently emerged as a promising candidate for nucleic acid amplification for molecular diagnostics, by virtue of its precise control over unit droplets without the need of any propulsion devices, ease of integration with chemical/biological reac-tions and multiplex assay capabilities. Nevertheless, current scientific research is still far from accomplishing the full potential of the technique, so new, innovative nanotechnology/biotech-nology hybrid approaches are necessary. As such, the purpose of this work is to contribute for the paradigm shift of nucleic acid amplification from central laboratories to point-of-care (POC) by designing and fabricating DMF devices compatible with isothermal nucleic acid amplifica-tion (loop-mediated isothermal amplification - LAMP). For biological validation of the devices, detection of cancer biomarker c-Myc is performed, and further real-time amplification moni-toring is attempted through several methodologies, namely fluorescence, impedance and elec-trochemical measurements. The DMF devices produced herein enable optimal temperature control, crucial for LAMP reactions, and further allow for a novel methodology of reagent mix-ing, based on dual actuation with back-and-forth motion and actuation frequency tuning. Such innovations lead to successful amplification of 0.5 ng/μL or 90 pg of c-Myc in one hour, in line with the range reported in the literature, and further monitoring of the LAMP reaction profile by microscopy-based fluorescence measurements. Impedimetric and electrochemical method-ologies did not meet the tight criteria required for biomarker detection, yet the developments achieved herein open the path for other applications. Lastly, the dielectric layer (key element of a DMF device) was optimized to assure long reactions (up to two hours) without device degradation.